Integration of Intellectual Property Rights and Cyber-Tech Soundness: A Pre-Requisite for National Interest (Journal of Intellectual Property Rights (JIPR), 2024)
Last two year's pandemic prompted a greater reliance on technology, as well as a greater usage of networked gadgets and hybrid work settings.Cybersecurity has developed into a complicated and rapidly evolving concern in the Information, Communication, and Technology (ICT) era. It seems that cyber threats will permeate every area of the economies and government infrastructures around the globe as the world's reliance on ICT increases. In fact, threats to a state's technology infrastructure that were previously unheard of, challenge national interest in the digital age. In the twenty-first century, cyber hazards are rapidly increasing and growing in the second decade. While criminals are still the ones who initiate them, other stakeholders, like foreign governments and political organizations, are also involved and may have objectives beyond money making as well. Back in 2020, the Indian government registered 1.16 million cyber security cases, a 3x increase over the previous years. Cyber-attacks in India, as in other nations, risk national security by gaining access to key government infrastructure. The scope of the cybersecurity danger is such that contemporary civilization might be described as being attacked holistically or systemically. To respond to a system-level danger, a system-level reaction will be required, so that the operations of various agencies and bodies complement each other and are mutually reinforcing, rather than competing. The current study recognizes intellectual property rights (IPR) to facilitate such requirement. The present research paper provides an insight of cyber security as a profound step towards securing the national interest, to its readers. It also makes an attempt to welcome intellectual property rights as a help towards achieving such a profound goal.